Curious George Goes Camping - Rey, H. A. (Hans Augusto); 1898- (Boston, Mass. : Houghton Mifflin, 1999)
Curious George gets into mischief while camping but is able to redeem himself in an emergency.
Keywords: Monkeys -- Juvenile fiction